Pre-eclampsia screening in the first trimester (Research, Society and Development, 2023)
The present study aimed to discuss pre-eclampsia screening in the first trimester of pregnancy. Pre-eclampsia is considered one of the main causes of maternal and fetal morbidity and mortality. Because of this, it is important to identify pregnant women at risk of developing preeclampsia during the first trimester of pregnancy, thus allowing for timely therapeutic intervention. Professional organizations such as the American College of Obstetricians and Gynecologists and the National Institute for Health and Care Excellence have proposed screening for preeclampsia based on maternal risk factors. However, few laboratory tests have high specificity and sensitivity to identify such pathology early. It is noteworthy that the Fetal Medicine Foundation's first trimester prediction model, which consists of a combination of maternal factors and measurements of mean arterial pressure, uterine artery pulsatility index, and serum placental growth factor, has undergone both internal and external validation as well. If successful, this screening test is superior to the traditional method (only for maternal risk factors). When identified, pregnant women at high risk of developing pre-eclampsia should use low-dose aspirin started before 16 weeks of gestation, as well as the use of calcium in pregnant women with low intake, aiming to reduce the rate of pre-eclampsia preterm. With that in mind, aiming at optimal screening performance, standardized protocols for measuring biomarkers and regularly assessing the quality of biomarkers should be established.